Indonesia's Diplomatic Strategy in Countering Vanuatu's Support for the Papuan Separatist Movement in the South Pacific - Setiawan, Dani Eka; Subanidja, Steph (Security Intelligence Terrorism Journal (SITJ), 2025)
This research analyzes Vanuatu's diplomatic strategy in supporting the separatist movement in Papua and Indonesia's response through intelligence and policy approaches. Using qualitative methods, data were collected through in-depth interviews with stakeholders, analysis of official documents, and participant observation. The results show that Vanuatu utilizes international forums such as the UN and the Melanesian Spearhead Group (MSG) to promote the Papuan issue, supported by a network of pro-independence activists. Indonesia responds through active diplomacy, counter-narratives, and increased economic cooperation with Pacific countries. Intelligence analysis identifies threats to national sovereignty, while policy recommendations emphasize a multilateral approach and strengthening domestic security. These findings contribute to the literature on separatist conflict management and the role of intelligence in foreign policy.